Jaringan Kerjasama Pengrajin Kecil Dan Pengusaha Studi Pada Sentra Industri Rumah Tangga Rebana Di Desa Kaliwadas, Kecamatan Bumiayu, Kabupaten Brebes - SARI, NOPA ITA; PARTINI, PARTINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study focuses on networking between home based worker and entrepreneurs in the home industry center of tambourine. Main purpose of this study is to understand and describe the networking between home based worker and entrepreneurs, as well as to understand the variation of the networking. The research is conducted in Kaliwadas Village, Bumiayu Subdistrict, Brebes Regency. The research method used was a descriptive study with a qualitative approach. The type of data that is collected primary and secondary data , primary data obtained through observation and in-depth interviews. While the secondary data obtained from government documents Kaliwadas village, the Internet, and vital records research. The unit of analysis of this study is the between home based worker and entrepreneurs. Data analysis was performed through three stages of data reduction (simplification of data ), data presentation and conclusion. The results of this study indicate that networking between home based worker and entrepreneurs occurs due to differences in the ownership of valuable resources (wealth, power, information ) as well as the constraints faced by home based worker such as the difficulty of wood raw materials, inclement weather, as well as the selling season tambourine. networking between home based worker and entrepreneurs are characterized by the presence of co-operation in the form of capital, raw materials and marketing. Entrepreneur as the owner of the capital markets a tambourine -owned home based worker, while the owners of s home based worker as a labor resource, collaboration is done by supplying the tambourine to entrepreneurs. There are variations of a networking between entrepreneurs with home based worker subscription and is not subscribed. Relations entrepreneurs with home based worker subscription is a patron - client relationship, while entrepreneurs with home based is not subscribed is more on the relationship tambourine purchase only (economics). In relationship with entrepreneurs, home based worker subscriptions are much more advantaged than the small craftsmen is not subscriptions. Home based worker subscriptions significantly received assurances can continue to produce tambourine and get protection and social security when were experiencing difficulties. While home based worker not a subscription small craftsmen able to survive but the business carried faltering because employers do not have the guarantee and the difficulty of absorbing losses of raw materials, adverse weather and lowering orders tambourine.